Translation Analysis On Adverb Of Manner In The Hunger Games Into The Hunger Games Novel By Hetih Rusli - A'INI, Fitria Nur; , Dr. Dwi Haryanti, M.Hum; , Drs. Sigit Haryanto, M. Hum (2015)
The purposes of this research are to classify the translation shifts of adverbs of manner in The Hunger Games Novel by Suzanne Collins and to explain the equivalence of adverb of manner in The Hunger Games Novel by Suzanne Collins. The type of this research is descriptive qualitative. The data of this research are the adverbs of manner found in The Hunger Games Novel by Suzanne Collins. The researcher uses documentation to collect the data. The researcher also uses comparative method to analyze the data of the research. The results of this research show that there are 247 data that found by researcher. First, the data of translation shifts belong to category shifts, there are 87 data or 35,22% ; 27 data or 10,93% adverb of manner is translated into adjective; 11 data or 4,45% adverb of manner is translated into verb; 2 data or 0,81% adverb of manner is translated into noun; 1 datum or 0,41% adverb of manner is translated into numeral; 46 data or 18,62% adverb of manner is not translated. Second , the data of translation shifts belong to level shifts, there are 160 data or 64,78% ; 136 data or 55,06% adverb of manner is translated into adverb phrase; 6 data or 2,43% adverb of manner is translated into adjective phrase, 8 data or 3,24% adverb of manner is translated into verb phrase, 7 data or 2,83% is translated into noun phrase, 3 data or 1,21% adverb of manner is translated into preposition phrase. The researcher also finds 229 data or 92,71% include equivalence of translation and 18 data or 7,29% include not-equivalent translation. Keyword: Translation, Adverb of Manner and Equivalence.